Post-impressionism - Wiggins, Colin (London ; New York : Dorling Kindersley, 1993)
A visual guide to the post-impressionist painters and the influences that shaped their work.
Young Cézanne -- Classical Seurat -- The Pointillists -- Van Gogh in Paris -- New light on the city -- Gauguin and Pont-Aven -- The symbolists -- The Nabis -- Thirst for publicity -- Lautrec's technique -- The new Renoir -- Rural idyll -- The grotesque -- Munch -- Rodin's sculpture -- Late Monet.
Includes index and glossary.
Book Report
Adult.
Keywords: Post-impressionism (Art) -- France; Painting, Modern -- 19th century -- France; Painting, Modern -- 20th century -- France; Post-impressionism (Art) -- Europe; Postimpressionism (Art); Painting, Modern -- 1800-1899 (19th century); Painting, Modern -- 1900-1999 (20th century)